Street railway equipment - Coxen, James R.; Jorgenson, Louis M.; Mallon, Carl E. (My University, 1907)
Introduction: Alternating current will perhaps in time supplant direct current for traction purposes as it did in lighting, with the advent of the long distance high potential transmission, but as yet the direct current plays a very important part in both power and traction. It has however the disadvantage of being difficult to transmit long distances without great loss. This is due to the inherent limitations in the production of high voltages from the direct current generator. Commutation at voltages sufficiently high to warrant economical transmission over long distances, is extremely difficult. Sparking and other difficulties at once arise which place the voltage within the limitations mentioned. The alternating current generator has not only the advantage of higher voltage, but by means of suitable transformer devices the voltage may be raised to any desired value for economical transmission. It will be readily seen, therefore, that alternating current machinery will supplant the direct current for traction purposes. In this thesis only direct current is treated. Direct current on a small scale and for local distribution fulfills more nearly the requirements demanded for traction purposes such as is needed on railways. The discussions are confined to the electrical equipment of the car only, the mechanical construction being referred to only as needed in line with the electrical connections.
Citation: Coxen, James R., Jorgenson, Louis M., and Mallon, Carl E. Street railway equipment. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Alternating Current; Street Car Motors; Direct Current; Theses